A Comprehensive Systematic Review of The Effectiveness of Rapid Diagnostic Tests for Tuberculosis in Resource Limited Settings - Yudha Viantoro; Fifa Yuniarmi (International Medical Journal Corp. Ltd, 2026)
Introduction: Tuberculosis (TB) remains a leading cause of mortality in resource-limited settings, where conventional diagnostic methods such as smear microscopy have suboptimal sensitivity and cannot detect drug resistance. Rapid diagnostic tests (RDTs) offering results within hours may address these limitations, but their effectiveness across diverse settings requires comprehensive evaluation. Methods: This review synthesized evidence from 126 studies conducted in low- and middle-income countries across Africa, Asia, and South America. Studies evaluating RDTs for active TB diagnosis against reference standards (culture, molecular tests, or clinical diagnosis) were included. Data extraction covered diagnostic accuracy, drug resistance detection, speed, implementation feasibility, cost factors, and clinical impact. Results: Xpert MTB/RIF demonstrated pooled sensitivity of 88-89% and specificity exceeding 98%, with substantial variation by smear status (98% in smear-positive vs 55-77% in smear-negative). Truenat assays showed comparable performance (90.6% sensitivity, 95.7% specificity), while TB-LAMP demonstrated 80% sensitivity and 98% specificity. Urine LAM testing achieved 66.7% sensitivity in severely immunocompromised HIV patients (CD4<50). For rifampicin resistance detection, Xpert MTB/RIF showed 94-95% sensitivity and 98% specificity. Time to results reduced from weeks to hours, with Xpert delivering results in <2 hours versus 16-30 days for culture. Implementation increased bacteriologically confirmed cases by 23-39% and reduced time to MDR-TB treatment from months to 22 days. Discussion: RDTs substantially improve TB detection over microscopy, particularly for smear-negative and drug-resistant cases. However, mortality benefits remain inconsistent, reflecting effective empirical treatment in control arms and persistent challenges in linkage to care. Cost and infrastructure requirements pose implementation barriers. Conclusion: RDTs are effective for TB diagnosis in resource-limited settings, but optimal impact requires integration into strengthened health systems with reliable treatment linkage.